EFFECT OF COASTAL SEDIMENT TO NUTRIENT AVAILABILITY AND MAIZE PRODUCTIVITY ON ENTISOLS - Suswati, Denah; Sagiman, Saeri; sulakhudin, Sulakhudin (AGRIVITA, Journal of Agricultural Science, 2015)
Entisols had a great potential for maize planting area expansion in increasing its production. The low soil fertility could be improved by application of coastal sediment. This current research examined the effect of different amount of coastal sediment on nutrient availability and maize production on Entisols, West Kalimantan. The research was conducted from July to November, 2013 in green house, Faculty of Agriculture, Tanjungpura University, West Kalimantan. The treatment conducted was the application of coastal sediment at dosage of: 0 Mg ha-1 (L0), 14 Mg ha-1 (L1), 28 Mg ha-1 (L2), 42 Mg ha-1 (L3), 56 Mg ha-1 (L4), 72 ton ha-1 (L5), 86 Mg ha-1 (L6) and 100 Mg ha-1 (L7). The treatments were arranged by completely randomized design with 3 replications. Research results showed that 42 Mg ha-1 coastal sediment was the best treatment and able to increase soil nutrients availability and maize productivity. The provision of coastal sediment increased the availability of K, Ca, Mg and Na, also the availability of nutrients in accordance with the increase of the dosage of coastal sediment.